Pengaruh Penyolderan Pada Kinerja Antena Multiple Input Multiple Output (MIMO) - Intan Aprillia Ikhsan (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2022)
To determine the performance of the antenna simulation results, fabrication and soldering processes are needed. The soldering process is the process of connecting two or more materials using tin or metal by heating. In this paper, the soldering process is carried out to connect the 50? SMA connector to the feed line and ground. The results of the rejection of the frequency in the simulation results from the range 5.2 – 6.1 GHz. For rejection frequency before soldering is 4.8 – 7.1 GHz. And after soldering the rejection of frequencies from the 4.2 – 5.5 GHz. The bandwidth deviation before and after soldering on the lower band 600 MHz and high band 1600 MHz.